Logistics and Supply Chains Through the Game - Kramar, Uroš (Strategije in pristopi večanja odpornosti in prožnosti oskrbovalnih verig, 2025)
In today's dynamic world, logistics and supply chains are key to the functioning of society and the economy. Games and simulations offer an interactive approach and allow participants to explore and develop logistics concepts and solutions for improvement. Focused on overcoming key logistics challenges, these games encourage innovation and waste recognition. In the context of supply chains, the games show the complex connections between different nodes and the challenges that arise due to potential disruptions. Among the popular games we can find the Beer distribution game, Paper or lego airplane game, Scum ball Game or Marshmallow Challenge. Through the tekst, we find that games and simulations are a valuable tool for researching and improving logistics and supply chains and greatly contribute to a better understanding of the key processes of the modern way of life.